Environmental and economic trade‐offs of using composted or stockpiled manure as partial substitute for synthetic fertilizer. Issue 4 (8th July 2021) - De Rosa, Daniele; Biala, Johannes; Nguyen, Trung H.; Mitchell, Elaine; Friedl, Johannes; Scheer, Clemens; Grace, Peter R.; Rowlings, David W.
Abstract: Manure generated from livestock production could represent an important source of plant nutrients in substitution of synthetic fertilizer. To evaluate the sustainability of partially substituting synthetic fertilizer with soil organic amendments (OAs) in horticulture, an economic and greenhouse gas (GHG) budget was developed. The boundary for analysis included manure processing (stockpiling vs. composting) and transport and spreading of manure and compost (feedlot and chicken) in intensively cultivated horticultural fields. The OA field application rates were calculated based on the nitrogen supplied by OAs. The GHG budget based on directly measured emissions indicates that the application of composted manure, in combination with reduced fertilizer rate, was always superior to stockpiled manures. Compost treatments showed from 9 to 90% less GHG emissions than stockpiled manure treatments. However, higher costs associated with the purchase and transport of composted manure (three times higher) generated a greater economic burden compared with stockpiled manure and synthetic fertilizer application. The plant nutrient replacement value of the OAs was considered only for the first year of application, and if long‐term nutrient release from OAs is taken into account, additional savings are possible. Because the income from soil carbon sequestration initiatives in response to OA application is unlikely to bridge this financial gap, particularly in the short term, this study proposes that future policy should develop methodologies for avoided GHG emissions from OA application. The combined income from soil carbon sequestration and potentially avoided GHG initiatives could incentivize farmers to adopt OAs as a substitute for synthetic fertilizers, thereby promoting more sustainable farming practices. Core Ideas: Soil organic amendments are a valid substitute for synthetic fertilizer. The use of compost rather than manure reduces GHG emissions from the manure supply chain. The reduction of fertilizer should be considered as an environmental credit.